Mekanisme Pendisiplinan Siswa di SMA Dalam Penegakan Tata Tertib Sekolah - Lisnawati; Nanang Martono; Elis Puspitasari (Jayapangus Press, 2023)
Various cases of violations of school rules show that one of the reasons is because students do not understand the contents of the rules. During this time students tend not to be involved in the formulation of the rules and only become the executor. This study aims to examine student involvement in enforcing school rules. This research was conducted using qualitative methods (field research) in a high school in Banyumas Regency, Central Java. Disciplining students at the school is a challenge in itself because most of the students come from the lower classes. The lower class is synonymous with harsh life demands that make it difficult to manage. Data was collected through interviews, observation, and documentation. The research targets were determined purposively, namely school principals, counseling teachers, and students (OSIS chairmen and students who often violate the rules). The results of the study show that teachers carry out a series of disciplines by collaborating with school organizations such as OSIS, MPK, and other organizational activists in the process of formulating rules through joint forums, dissemination of rules offline and online, supervising students during departures and raids, and assessing student discipline individual or collective (class). Based on this, it can be concluded that the school has provided an open space for students to be involved in disciplinary mechanisms from the formulation to the implementation of school rules.